FAMILY LITERACY-BASED APPROACH TO STRENGTHENING SELF-CARE MANAGEMENT COMPLIANCE IN DIABETES MELLITUS PATIENTS: INSIGHTS FROM A HOSPITAL STUDY. - Rachmawaty M. Noer; Sri Herti Naulina Simatupang; Collene Fathona; Mira Agusthia (Poltekkes Kemenkes Banten, 2026)
Self care. management in patients with diabetes mellitus, which is an effort that can be made by patients with diabetes mellitus to be able to manage themselves which is influenced by family support and health literacy. This study was conducted to determine the Relationship between Family Support and Health Literacy with Self care. management Compliance in Patients with Diabetes Mellitus in the Edelweis Room of X Batam Hospital in 2024. This study used a quantitative method with 30 respondents of Patients with Diabetes Mellitus in the Edelweis Room of X Batam Hospital using consecutive sampling techniques. Data were processed using the Chi Square test. The results of the study obtained the largest respondent support in the poor category as many as 18 respondents (60%), the largest respondent Health literacy in the inadequate category as many as 20 respondents (66.7%), Self Care Management of the largest respondents in the poor category as many as 16 respondents (53.3%), There is a Relationship between Family Support and Self Care Management in Diabetic Mellitus Patients with a p value of 0.02, There is a Relationship between Health literacy and Self Care Management in Diabetic Mellitus Patients with a p value of 0.019. This study can provide better knowledge to patients about the importance of family support, health literacy, and DM selfcare management to improve health levels.